DEVELOPMENT OF WEB-BASED REPOSITORY TECHNOLOGY FOR LECTURER'S PERFORMANCE MONITORING - Rony, Muhammad Ainur; Anggraeni, Motika Dian (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
Higher education performance assessment on Accreditation requires the results and evidence of lecturer performance. Currently, the Faculty is already using FTP and Google Drive technology. However, the weakness of using these technologies is that the Faculty still has to process data manually, so it is not effective and efficient. Therefore we need technology that can help effectively and efficiently monitor and record performance along with supporting document evidence. With this web repository, the Faculty can monitor and, at the same time, be able to draw supporting evidence for the preparation of accreditation forms. The research method used in this study is a combination method between Design Thinking and Scrum methods as a method for application development.